Asset Forfeiture from Human Trafficking - Petrunov, Georgi (Research Papers, 2018)
Human trafficking is a global problem generating huge illicit incomes. Based on the notion that the opportunities for fast and large profits are the main drive for committing crimes, in this article we focus on the asset forfeiture from trafficking of human beings as an efficient tool to fight this criminal business. Using secondary analysis of documents and statistical data we come to the conclusion that the application of this instrument is still very limited in the practice of the Bulgarian law-enforcement institutions. The insufficient institutional application in turn deprives the state of key weapon in the arsenal, aimed to effectively combat crime.
Keywords: Money laundering; Asset forfeiture; Human trafficking